Proceedings of the 15th International Conference on Ground Penetrating Radar 2014
DOI: 10.1109/icgpr.2014.6970403
|View full text |Cite
|
Sign up to set email alerts
|

Soil piping: networks characterization using ground-penetrating radar

Abstract: Soil plpmg remains a relatively unexplored phenomenon despite its substantial impacts on watershed scale water and sediments transfer in numerous locations around the world. One of the main limits regarding the study of this singular process is characterization of the pipe networks (defining number, position, dimension and connectivity of pipes). In this context, non-invasive sub surface imaging using ground-penetrating radar (GPR) seems a promising technique. An exploratory methodology was developed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This study in a complex way has confirmed that GPR can be used to detect soil pipes: this is in accordance with previous reports [7,[18][19][20][21]. The reflections on radargrams that indicate soil pipes are well visible because there are significant differences in radar-wave response given by pipes filled with air and with water at the bottom (Figures 4e, 7d and 10c), and with the surrounding soil.…”
Section: Suitability Of Gpr Application For Soil Pipe Detectionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study in a complex way has confirmed that GPR can be used to detect soil pipes: this is in accordance with previous reports [7,[18][19][20][21]. The reflections on radargrams that indicate soil pipes are well visible because there are significant differences in radar-wave response given by pipes filled with air and with water at the bottom (Figures 4e, 7d and 10c), and with the surrounding soil.…”
Section: Suitability Of Gpr Application For Soil Pipe Detectionsupporting
confidence: 91%
“…The soil pipes were filled with air, and in the bottom the increased soil moisture and water were present. These subsurface tunnels are reflected on radargrams as reflection hyperbolas when they are crossed transversely, as singular strong reflections [18], or as an anomaly in the reflections [8]. All reflections that might potentially suggest pipe occurrence were interpreted in their relation to others within a profile, or between two consecutive profiles and they were related to the surface indicators of piping (i.e., sagging of the ground or pipe roof collapses).…”
Section: Ground-penetrating Radar Surveymentioning
confidence: 99%
See 3 more Smart Citations